The interplay of parental financial behaviour and financial literacy and the moderating effects of parental income - Adam Ndou (Global Business & Finance Review (GBFR), 2023)
Purpose: The moderating effect of parental income on parental financial behaviour and financial literacy is increasingly becoming important. The objective of this study was to determine whether the relationship between parental financial behaviour and financial literacy of young adults is moderated by parental income. Design/methodology/approach: Financial literacy was measured through financial knowledge, financial behaviour, financial attitudes, and financial decision-making. Quantitative research approach was adopted for this study. Self-administered questionnaire was used to collect data among young adults in South Africa. Moderated regression analysis was used to analyse data. Four hypotheses were tested. Findings: The results showed that Parental income moderated the relationship of Parental financial behaviour with financial behaviour, financial attitude, and financial decision-making. Furthermore, the results indicated that parental income did not moderate the relationship of Parental financial behaviour and financial knowledge. Therefore, the overall results indicated that the relationship between parental financial behaviour and financial literacy is moderated by parental income. Research limitations/implications: Due to the low levels of general literacy among the respondents, which negatively affected data collection; some young adults did not understand the questionnaire and withdrew from participating in the study. Furthermore, even though confidentiality and anonymity were guaranteed, respondents were reluctant to participate in the study. They feared exposing their financial position and displayed a lack of trust. Originality/value: This study is amongst the first to investigate whether the relationship between parental financial behaviour and financial literacy is moderated by parental income. This study concluded by providing recommendations and suggestions for future research.
Keywords: 650; Parents; Financial behaviour; Parental income; Financial literacy